Extemporaneous preparation of rifampicin granules from capsules to improve usability. Issue 1 (18th August 2021) - Miyazaki, Yasunori; Uchino, Tomonobu; Kagawa, Yoshiyuki
Abstract : Objectives: Manipulation of tablets or capsules is frequently carried out in pharmacies to regulate doses for personalised therapy. We proposed the use of reconstructed granules as a suitable, flexible dosage form and developed an on-site granulation method using a compounding mixer. The aim of this study was to demonstrate the feasibility of small-scale preparation of granules in a pharmacy setting. Rifampicin capsules were used as a model medicine because of the associated need for drug desensitisation therapy. Methods: The contents of a rifampicin capsule were granulated using a compounding mixer, and small ointment containers (12 mL) with filling rates of 4%, 8%, 12%, and 16% were used as granulation vessels. The obtained granules were examined for particle size distribution, yield, crystal transition, drug dissolution profile, storage stability, and weight loss during dosing. Results: The yields increased by >95%, and the span of the particle size distribution decreased to 1.0, as the filling rate increased. The smallest batch size was found to be 0.8 g in a 12 mL vessel. Examination of the resultant granules revealed that granulation did not affect the crystal polymorphism, dissolution profile, or storage stability of rifampicin. Furthermore, the weight loss of the granules during the dosing process was significantly lower than that of the capsule powder content. Conclusions: We demonstrated that granules with sufficient quality for clinical use could be extemporaneously prepared using a compounding mixer in pharmacies. This improved the usability of the medicine, preventing weight loss, and making it a suitable alternative formulation for precise personalised pharmacotherapy.